NARRATIVE MODES IN THE NOVELS OF YASMINAKHADRA - Dr. C. S. Arunprabu, Dr. K. Kaviarasu, Dr. S. Poornima (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Narratives in corporate elements like verisimilitude, focalisation, character, types of narration and so on. The author expresses his ideas through various modes of narration. The stye of narration and the narrative tools differ from one text to the other, but certain tools like analepsis, prolepsis, in medias res and characterisation remains common in most of the literary work of art. Each of his novels exhibits various modes of narration. Hence the authorial narrative stands explicit throughout YasminaKhadra’s seminal works.